2021
DOI: 10.1111/tid.13559
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal candidiasis outcomes in renal transplant recipients receiving nystatin versus no antifungal prophylaxis

Abstract: Oropharyngeal candidiasis, or OC, is a fungal infection associated with immunosuppression among solid organ transplant recipients. [1][2][3][4][5][6] OC presents as soft yellowish-white plaques or diffuse erythematous patches on the oral mucosa, which can cause patients to experience a cottony feeling in the mouth, altered taste and sense of smell, odynophagia, and dysphagia. 4 OC development can predispose patients to more severe manifestations such as esophageal candidiasis and disseminated Candida infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The decision to stop using clotrimazole prophylaxis did not have clinical impact on candidiasis as there was not a statistically significant difference in its incidence between groups, although there were more cases of oropharyngeal candidiasis among those who did not receive prophylaxis (4.3% incidence). This observed incidence is lower than that seen in a similar single‐center study conducted by Ky et al., in which oropharyngeal candidiasis within 3 months post‐kidney transplant was seen in 7.8% of those not receiving nystatin prophylaxis 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision to stop using clotrimazole prophylaxis did not have clinical impact on candidiasis as there was not a statistically significant difference in its incidence between groups, although there were more cases of oropharyngeal candidiasis among those who did not receive prophylaxis (4.3% incidence). This observed incidence is lower than that seen in a similar single‐center study conducted by Ky et al., in which oropharyngeal candidiasis within 3 months post‐kidney transplant was seen in 7.8% of those not receiving nystatin prophylaxis 10 …”
Section: Discussionmentioning
confidence: 99%
“…This observed incidence is lower than that seen in a similar single-center study conducted by Ky et al, in which oropharyngeal candidiasis within 3 months post-kidney transplant was seen in 7.8% of those not receiving nystatin prophylaxis. 10 An inherent limitation of this study is its retrospective design, which limited the overall sample size and the ability to control for adjustments in tacrolimus dosing. Specifically, adjustments between the time of tacrolimus initiation and first recorded trough, as well as adjustments between the time of clotrimazole discontinuation and the first recorded trough post-discontinuation were unable to be captured.…”
Section: Discussionmentioning
confidence: 99%
“…At our hospital, we do not perform candidiasis prophylaxis early after transplantation. Previous reports have indicated that prophylactic administration of antifungal drugs is non‐inferior with respect to the development of oral candidiasis 12 . However, it is possible that over‐immunosuppressive conditions may be overlooked in facilities where antifungal drugs are administered prophylactically after kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%